Chemical peritonitis resulting from spontaneous rupture of a mature ovarian cystic teratoma: a case report - Bužinskienė, Diana; Mongirdas, Matas; Mikėnas, Saulius; Drąsutienė, Gražina; Andreika, Linas; Sakalauskaitė, Indrė (Acta medica Lituanica, 2020)
Background. Mature cystic teratomas (dermoid cysts) are the most common germ cell tumours with 10–25% incidence of adult and 50% of paediatric ovarian tumours. The aetiology of dermoid cysts is still unclear, although currently the parthenogenic theory is most widely accepted. The tumour is slow-growing and in the majority of cases it is an accidental finding. Presenting symptoms are vague and nonspecific. The main complication of a dermoid cyst is cyst torsion (15%); other reported complications include malignant transformation (1–2%), infection (1%), and rupture (0.3–2%). Prolonged pressure during pregnancy, torsion with infarction, or a direct trauma are the main risk factors for a spontaneous dermoid rupture that can lead to acute or chronic peritonitis. The diagnosis of mature cystic teratoma is often made in retrospect after surgical resection of an ovarian cyst, because such imaging modalities as ultrasound, computer tomography, or magnetic resonance imaging cannot yet accurately and reliably distinguish between benign and malignant pathology. Materials and methods. We present a report of a clinical case of a 35-years-old female, who was referred to the hospital due to abdominal pain spreading to her feet for three successive days. She had a history of a normal vaginal delivery one month before. Abdominal examination revealed mild tenderness in the lower abdomen; no obvious muscle rigidity was noted. Transvaginal ultrasound showed a multiloculated cystic mass measuring 16 × 10 cm in the pelvis. In the absence of urgency, planned surgical treatment was recommended. The next day the patient was referred to the hospital again, with a complaint of stronger abdominal pain (7/10), nausea, and vomiting. This time abdominal examination revealed symptoms of acute peritonitis. The ultrasound scan differed from the previous one. This time, the transvaginal ultrasound scan revealed abnormally changed ovaries bilaterally. There was a large amount of free fluid in the abdominal cavity. The patient was operated on – left laparoscopic cystectomy and right adnexectomy were performed. Postoperative antibacterial treatment, infusion of fluids, painkillers, prophylaxis of the thromboembolism were administered. The patient was discharged from the hospital on the seventh postoperative day and was sent for outpatient observation. Results and conclusions. Ultrasound is the imaging modality of choice for a dermoid cyst because it is safe, non-invasive, and quick to perform. Leakage or spillage of dermoid cyst contents can cause chemical peritonitis, which is an aseptic inflammatory peritoneal reaction. Once a rupture of an ovarian cystic teratoma is diagnosed, immediate surgical intervention with prompt removal of the spontaneously ruptured ovarian cyst and thorough peritoneal lavage are required.
Keywords: chemical peritonitis; dermoid cyst; mature cystic teratoma; peritoneal lavage; spontaneous rupture